Shaping tales - Pillai, Kaysie Kai Sze (2019)
Shaping Tales is an interactive project that presents a new take on the way patterns can be perceived and interpreted through the translation and revisualisation of stories into shapes and patterns. It is a play on the relationship between two generic terms “patterns” and “stories”. Research of various forms and aspects of patterns from different time periods and cultures have been compared to that of various narratives. This has as such led to the proposition that patterns are stories in their own way. Patterns in this project are henceforth presented not simply as a design or decoration as previously known but as a narrative. Words from stories and texts are converted and generated into patterns following a set of parameters byway of a custom computer programme. Viewers are then encouraged to partake in this work much like a game creating their own narratives or modifying someone else’s narrative. Unique patterns are created as a result of the story being created in real time. Participation thus helps to further emphasise the similarities between patterns and stories and also introduce this new perspective to the audience. The result of this project is a newly defined connection between patterns and narratives that begins to take its shape.